Consumer Behaviour in Rural Areas: A Microlevel Study on Buying Behaviour of Rural Consumers in Kavali Mandal - Nagaraja, B. (Indian Journal of Marketing, 2004)
In recent days, consumer India is at the point where there is a multiplicative effect of income growth, aspiration to consume and a changed consumption friendly ideology/social discourse across the income board, especially in rural India. Hence, the buying behaviour of rural consumers has became a hot-topic for discussion because rural India, in recent days, is enthusiastically consuming everything from shampoo to motor cycles and this "rural predilection" is being considered as one of the significant topics of market analysis. Besides, we know well that purchase decisions in Indian homes have become a collective process, with women and teenage children playing a major role on product and 'brand choices'. Decision-making has become a joint process in the family. Woman is the initiator and product evaluator, man the financier and child, an influencer. Hence, the market analysts are adopting both the" product window" approach and "Consumer or People Window" approach for getting an insight into the structure and drivers of consumer demand particularly in rural India. The first approach deals with the perspective of" how much of what is being bought" and the latter deals with " how many of what kind of people are buying". The thrust is on not just what is being bought but also who is buying and the analysis has to be made considering both "product segments" and "consumer segments".